New Boolean Equation for Orthogonalizing of Disjunctive Normal Form based on the Method of Orthogonalizing Difference-Building - Can, Yavuz; Kassim, Hassen; Fischer, Georg (Journal of Electronic Testing-Theory and Applications, 2016)
In this paper a new Boolean equation for the orthogonalization of Boolean functions respectively of Ternary-Vector-Lists of disjunctive normal form is presented. It provides the mathematical solution of orthogonalization for the first time. The new equation is based on the new method of orthogonalizing difference-building ⊖. In contrast to other methods the new method has a faster computation time. Another advantage is the smaller number of product terms respectively of Ternary-Vectors in the orthogonalized result in contrast to other methods. Furthermore, the new equation can be used as a part in the calculation procedure of getting suitable test patterns for combinatorial circuits for verifying feasible logical faults.
Keywords: Orthogonalizing Boolean Forms